2014
DOI: 10.1002/lary.24917
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of dysphagia in older patients evaluated at a tertiary center

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…The items “Swallowing solids takes extra effort” and “Swallowing pills takes extra effort” were most often rated as a problem. Swallowing solids or pills are known to be common clinical complaints for people with dysphagia [50, 51]. The items “My swallowing problem has caused me to lose weight” and “Swallowing is painful” were most often rated as no problem.…”
Section: Discussionmentioning
confidence: 99%
“…The items “Swallowing solids takes extra effort” and “Swallowing pills takes extra effort” were most often rated as a problem. Swallowing solids or pills are known to be common clinical complaints for people with dysphagia [50, 51]. The items “My swallowing problem has caused me to lose weight” and “Swallowing is painful” were most often rated as no problem.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, microplasmin was reported to cure focal vitreomacular adhesion as tested in two MIVI-TRUST phase III clinical trials. The trials demonstrated that microplasmin can resolve vitreomacular adhesion and cure full thickness macular hole and vision impairments and that it is safe and well-tolerated [ 71 , 72 ].…”
Section: Therapeutic Approaches and Their Current Delivery Systemmentioning
confidence: 99%
“…Dysphagia, which is a common disorder in the elderly [8], is also considered a risk factor for aspiration pneumonia [6,9,10]. It has been reported that approximately 15%-40% of the elderly population over 65 years is affected by dysphagia [11,12], and 55% of elderly adults 70 years and older diagnosed with pneumonia presented with clini cal signs of oropharyngeal dysphagia [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that approximately 15%-40% of the elderly population over 65 years is affected by dysphagia [11,12], and 55% of elderly adults 70 years and older diagnosed with pneumonia presented with clini cal signs of oropharyngeal dysphagia [13]. Only 20% of older patients with aspiration symptoms exhibit normal swallowing function in a videofluoroscopic swallowing study (VFSS), and laryngeal penetration is identified in approximately 40% and aspiration in 20% [8]. A previous study reported that oropharyngeal dysphagia is closely related to community-acquired pneumonia in elderly subjects regardless of functional status and comorbidities [9].…”
Section: Introductionmentioning
confidence: 99%